KONSEP JUAL BELI BERBASIS ONLINE DALAM TINJAUAN EKONOMI ISLAM - Nabbila, Faricha Lita; Yuliani, Yuliani (Lembaga Pengembangan Kinerja Dosen, 2023)
Buying and selling online has become a craze of the community and is done by almost everyone in selling or buying goods. The concept of buying and selling online is also not difficult, it can be done at home and you only need to prepare data and Wi-Fi and then have online stores such as Tokopedia, Shopee, Open Stalls, Lazada, Bli Bli or other types of stores on other application platforms. The process of selecting goods, making payments, until the goods arrive, all systems are carried out online without face-to-face meetings between sellers and buyers. This research was conducted to find out whether the concept of buying and selling online is permissible in Islam. This study uses a descriptive analysis method with data obtained from related literary sources. Data was collected through literature study from journals, books, reports and other sources related to the Online Buying and Selling Concept. Given the rapid development of online business, the authors are interested in examining more about the concept of buying and selling online and how buying and selling online does not come out of the corridors of Islamic law.